Convention Dan Exhibition Centre Di Solo Baru Penekanan Pada Arsitektur Modern Kontemporer - Utomo, Danan Dwi, Dr. Ir. W. Nurjayanti, MT, Ir. Nurhasan, MT (2015)
Convention and Exhibition Centre in New Solo emphasis on Contemporary Modern architecture is a building of container central coordination of activities related to the conference and exhibition which provide facilities and ingredients in Solo Baru with emphasis on to form follow function (form follows function) with a contemporary design more advanced, varied, flexible, and innovative. Background didirikanya Convention and Exhibition Centre in New Solo due to the development of culture and civilization that mengingkat in the 21st century raises a number of discoveries and problems along the penyelesaianya needs to be known and addressed by mankind. Dissemination and exchange information and new things and the problems that are universal against interests other than through the mass media, can also through the conventions and exhibits both international, national, and regional. Organizing convention and exhibition is expected to be dynamic factor for the development of the economic industry. From the context of the above relationship it can be seen that the activities of the convention and exhibition business activities. Coupled with New Solo potential increase in trade and industry sector. With the point of supporting activities / building support Convention and Exhibition Centre in New Solo. The absence of a building that Convention and Exhibition Centre Special facilitate the activities of the convention and exhibition that provides facilities and New Solo ingredients. Of the potential of Solo Baru, the Convention and New Solo Exhibition Centre in a very precise set in New Solo and future prospects expected to overcome the obstacles that exist for development and progress of New Solo. Convention and Exhibition Centre in New Solo emphasis on Contemporary Modern architecture is a building of container central coordination of activities related to the conference and exhibition which provide facilities and ingredients in Solo Baru with emphasis on to form follow function (form follows function) with a contemporary design more advanced, varied, flexible, and innovative. Background didirikanya Convention and Exhibition Centre in New Solo due to the development of culture and civilization that mengingkat in the 21st century raises a number of discoveries and problems along the penyelesaianya needs to be known and addressed by mankind. Dissemination and exchange information and new things and the problems that are universal against interests other than through the mass media, can also through the conventions and exhibits both international, national, and regional. Organizing convention and exhibition is expected to be dynamic factor for the development of the economic industry. From the context of the above relationship it can be seen that the activities of the convention and exhibition business activities. Coupled with New Solo potential increase in trade and industry sector. With the point of supporting activities / building support Convention and Exhibition Centre in New Solo. The absence of a building that Convention and Exhibition Centre Special facilitate the activities of the convention and exhibition that provides facilities and New Solo ingredients. Of the potential of Solo Baru, the Convention and New Solo Exhibition Centre in a very precise set in New Solo and future prospects expected to overcome the obstacles that exist for development and progress of New Solo.